A coupled thermo- hydro-mechanical simulation of reservoir CO2 enhanced oil recovery. Issue 5 (August 2016) - Elyasi, Ayub; Goshtasbi, Kamran; Hashemolhosseini, Hamid
Carbon dioxide sequestration is an effective mechanism for enhanced oil recovery. In a carbon dioxide enhanced oil recovery project, the temperature of the injected carbon dioxide is usually considerably lower than the formation temperature. The heat transfer between the injected fluid, reservoir fluids, and rock has to be investigated in order to test the viability of the target formation to act as an effective enhanced oil recovery unit and to optimize the process. Simulation of carbon dioxide injection based on a suitable modeling is very important for explaining the fluid flow behavior of carbon dioxide in a reservoir. Geomechanical aspects between fluids and carbonate rocks can change porosity and permeability during carbon dioxide flooding which may significantly impact well injectivity, reservoir integrity, and oil recovery. This article presents development of a simulator using implementation of a program (FORTRAN 90 interface code) for coupled thermo-hydro-mechanical processes in multiphase reservoir modeling. The simulator is denoted ECLIPSE-ABAQUS, because it utilizes two established computer codes, ECLIPSE and ABAQUS, which are linked and jointly executed for analysis of coupled thermo-hydro-mechanical processes. The capabilities of the ECLIPSE-ABAQUS simulator are demonstrated on a complex coupled problems related to injection of carbon dioxide in an oil reservoir. The coupled thermo-hydro-mechanical analysis of the reservoir showed that the reservoir production rate/total and production time in the coupled thermo-hydro-mechanical simulation is more than the uncoupled one. Also permeability and porosity changes in the coupled thermo-hydro-mechanical simulation are different from the coupled hydro-mechanical simulation. Furthermore, the Finite Element Method analysis showed no sign of plastic strain under production and carbon dioxide injection scenarios in any part of the reservoir.